EDUCAÇÃO EM DIREITOS HUMANOS COMO INSTRUMENTO DE TRANSFORMAÇÃO SOCIAL - Fernanda Baldanza; Reis Friede (TRF2, 2018)
The World Conference on Human Rights considered that human rights education, training and public information are indispensable for establishing and promoting stable and harmonious relationships between communities and for fostering mutual understanding, tolerance and peace. The global factual context regarding the protection of human rights still faces many obstacles to the recognition of such rights, especially in groups that are vulnerable. This essay deals with the legal-normative point of view of human rights education in Brazil.In order to do so, this paper analyzes the main international documents on Human Rights Education and, afterwards, studies the Brazilian normative framework in the matter of Human Rights. It concludes, finally, that a new form of education must be conceived, directed to the construction of a humanist thought in its essence, ideologically and behaviorally based.